Positional identification of hypertension susceptibility genes on chromosome 2 - Barkley, Ruth Ann; Chakravarti, Aravinda; Cooper, Richard S; Ellison, R Curtis; Hunt, Steven C; Province, Michael A; Turner, Stephen T; Weder, Alan B; Boerwinkle, Eric (Hypertension (Dallas, Tex. 1979), 2004)
Chromosome 2 has been consistently identified as a genomic region with genetic linkage evidence suggesting that one or more loci contributes to blood pressure and hypertension status. As with all complex disease traits, following-up linkage evidence to identify the underlying susceptibility gene(s) is an arduous yet biologically and clinically important task. Using combined positional candidate gene methods, the Family Blood Pressure Program (FBPP) has concentrated efforts in narrowing a large region of chromosome 2, demonstrating evidence for linkage in several populations, and identifying underlying candidate hypertension susceptibility gene(s). Initial informatics efforts identified the boundaries of the region and the known genes within it. A total of 82 polymorphic sites in 8 genes were genotyped in a large hypothesis-generating sample consisting of 1640 African Americans, 1339 whites, and 1616 Mexican Americans. After resampling-based false discovery adjustment, SLC4A5, a sodium bicarbonate transporter, was identified as a primary candidate gene for hypertension. Polymorphisms in SLC4A5 were subsequently genotyped and analyzed for validation in two other subcomponents of the FBPP, each contributing African Americans (N=461; N=778) and whites (N=550; N=967). Again, single nucleotide polymorphisms within this gene were significantly associated with blood pressure levels and hypertension status. Although not identifying a single causal gene variant that is significantly associated with blood pressure levels and hypertension status across all samples, the results further implicate SLC4A5 as a candidate hypertension susceptibility gene. Moreover, the present study validates previous evidence for one or more genes on chromosome 2 that influence hypertension-related phenotypes in the population-at-large.